The diversity of secondary metabolites in Indonesian soybean genotypes - ERIYANTO YUSNAWAN (Biodiversitas Journal of Biological Diversity, 2016)
Yusnawan E. 2016. The diversity of secondary metabolites in Indonesian soybean genotypes. Biodiversitas 17: 704-710. Soybean secondary metabolites protect the crop from pathogen infection. These secondary metabolites especially phenolic compounds also have functional properties.This study aimed to determine total phenolic and flavonoid contents as well as antioxidant activity of Indonesian soybean genotypes. A total of 63 soybean genotypes with four different seed coat colors (green yellow, light yellow, yellow, and black) and different seed sizes (small, medium and large) was used in this study. Total phenolic content was measured using Folin- Ciocalteu’s reagent and antioxidant activity was determined with 2,2-diphenyl-1-picrylhydrazyl. All six genotypes with black seed coat color had higher total phenolic and flavonoid contents as well as antioxidant activity than those in other colors’ genotypes. Total phenolic contents of those six black soybeans ranged from 7.19 to 14.72 mg gallic acid equivalent per gram and total flavonoid contents varied from 1.91 to 5.30 mg catechin equivalent per gram. Antioxidant activities of these genotypes ranged from 10.99 to 20.38 μmol trolox equivalent per gram. An estimation of the total phenolic contents as well as antioxidant activities particularly in black soybeans was valuable and important for seeking soybeans with high antioxidant properties.